2022
DOI: 10.3389/fpls.2021.712363
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Biochemistry-Combined Transcriptomic Analysis Reveals Mechanism of Bacillus cereus G2 Improved Salt-Stress Tolerance of Glycyrrhiza uralensis Fisch. Seedlings by Balancing Carbohydrate Metabolism

Abstract: Salt stress severely threatens the growth and productivity of Glycyrrhiza uralensis. Previous results found that Bacillus cereus G2 enhanced several carbohydrate contents in G. uralensis under salt stress. Here, we analyzed the changes in parameters related to growth, photosynthesis, carbohydrate transformation, and the glycolysis Embden-Meyerhof-Parnas (EMP) pathway-tricarboxylic acid (TCA) cycle by G2 in G. uralensis under salt stress. Results showed that G2 helped G. uralensis-accumulating photosynthetic pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 71 publications
1
5
0
Order By: Relevance
“…PGPR can generate exopolysaccharides, which enhance soil structure, increase the availability of soil water, improving plant physiological characteristics, such as chlorophyll content, particularly under stress conditions (Tank and Saraf, 2010;ALKahtani et al, 2020). In recent years, researchers have gradually begun to study the effect of PGPR on plant molecular responses through the use of the transcriptome method, with the final objective of improving plant salt tolerance (Wang Y. et al, 2022;Xiao et al, 2022). The investigation of the transcriptome-wide response of M. uniflorum leaves revealed that PG-4-initiated salt tolerance is likely attributed to the regulation of several key biological processes, such as stress signaling components and regulators, plant hormone signal transduction and putative regulators of cell wall organization.…”
Section: Discussionmentioning
confidence: 99%
“…PGPR can generate exopolysaccharides, which enhance soil structure, increase the availability of soil water, improving plant physiological characteristics, such as chlorophyll content, particularly under stress conditions (Tank and Saraf, 2010;ALKahtani et al, 2020). In recent years, researchers have gradually begun to study the effect of PGPR on plant molecular responses through the use of the transcriptome method, with the final objective of improving plant salt tolerance (Wang Y. et al, 2022;Xiao et al, 2022). The investigation of the transcriptome-wide response of M. uniflorum leaves revealed that PG-4-initiated salt tolerance is likely attributed to the regulation of several key biological processes, such as stress signaling components and regulators, plant hormone signal transduction and putative regulators of cell wall organization.…”
Section: Discussionmentioning
confidence: 99%
“…One of the key steps in this process involves the conversion of pyruvate, a critical metabolic intermediate, into acetyl-CoA. This conversion is driven by the concerted action of two enzymes, pyruvate dehydrogenase and lactose dehydrogenase [ 46 ]. Once acetyl-CoA is formed, it is further processed through a series of additional metabolic reactions, including the action of acetate kinase and phosphotransferase, to ultimately produce acetic acid [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the YL, most of the carbohydrates in the SCs were downregulated, while myo-inositol was significantly upregulated. Resistance to external stress through inositol upregulation in plant cells has been reported [ 34 ], as inositol acts as a precursor substance for a variety of important metabolites involved in a variety of physiological and biochemical processes, such as growth regulation, cell membrane formation, hormone regulation, programmed cell death, stress signaling, and cellular immunity, among other metabolic pathways [ 35 ]. In addition, it is noteworthy that the key genes in the glyoxylate cycle and dicarboxylic acid metabolic pathways were significantly upregulated in the carbohydrate metabolic pathway enriched by the SCs, while the key genes in the TCA cycle pathway were significantly downregulated.…”
Section: Discussionmentioning
confidence: 99%